Natural resource accounting and economic development - Perrings, Charles; Vincent, Jeffrey R. (Cheltenham, UK ; Northhampton, MA, USA : E. Elgar Pub., 2003)
The book makes a substantial contribution to the development of an important field of environmental economics. It should be read by all environment and development economists, and policymakers with a particular interest in natural resource accounting, sustainability and development.
Includes bibliographical references and index.
gau 27/01/14
Loans
Keywords: Natural resources -- Accounting; Economic development